2003
DOI: 10.1159/000073959
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Adenosine Triphosphate-MgCl<sub>2</sub> on Ischemia-Reperfusion Lung Injury Is Leukocyte Dependent

Abstract: Adenosine triphosphate (ATP)-MgCl2 attenuates ischemia-reperfusion (I-R)-induced lung injury in rats. A previous study indirectly suggests that Mg2+-dependent ecto-ATPases on the surface of leukocytes are responsible for the hydrolysis of ATP-MgCl2 to adenosine, which then contributes to the protective effect of ATP-MgCl2. This study investigated the role of leukocytes in I-R injury and the protective effect of ATP-MgCl2 in our buffer-perfused isolated rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A previous study [14] indirectly suggested that Mg 2+ -dependent ecto-ATPases on the surface of leukocytes are responsible for the hydrolysis of ATP-MgCl 2 to adenosine, which then contributes to the protective effect of ATPMgCl 2 . Chen et al [7], in a buffer-perfused isolated rat lung model, found that ischemia-reperfusion increases capillary permeability, lung weight gain, wet lung/body weight ratio, lung lavaged protein concen-…”
Section: Protective Effect Of Atp-mgcl 2 On Ischemia-reperfusion Lungmentioning
confidence: 99%
“…A previous study [14] indirectly suggested that Mg 2+ -dependent ecto-ATPases on the surface of leukocytes are responsible for the hydrolysis of ATP-MgCl 2 to adenosine, which then contributes to the protective effect of ATPMgCl 2 . Chen et al [7], in a buffer-perfused isolated rat lung model, found that ischemia-reperfusion increases capillary permeability, lung weight gain, wet lung/body weight ratio, lung lavaged protein concen-…”
Section: Protective Effect Of Atp-mgcl 2 On Ischemia-reperfusion Lungmentioning
confidence: 99%